Teaching-Learning Process Self-Efficacy Beliefs Scale (TLPSEBS) for Academic Staff: A Scale Development Study - Uygur, Mutlu; Yelken, Tuğba Yanpar (Asian Journal of Education and Training, 2020)
A valid and reliable measurement tool has been developed to measure the teaching-learning process self-efficacy of instructors in higher education institutions. During the scale development stage, the scale form was e-mailed to 305 instructors, who were selected through purposive sampling method, working at the faculties of health, social, science, fine arts and engineering of the randomly determined universities in 7 regions of Turkey. As a result of the explanatory factor analysis, the 8 items were excluded from the scale and the single-factor scale with remaining 40 items explained 58,309% of the total variance. The internal consistency coefficient (Cronbach’s Alpha) of the scale was found to be .98 for the whole scale. It was concluded according to these findings that the scale developed in this study is a valid and reliable measurement tool that can be used to measure the teaching-learning process self-efficacy of the instructors working in higher education institutions.